THE EFFECTIVENESS OF EWA (ENGLISH WITH APPS) TO IMPROVE READING SKILLS - Sari Wulan; Urai Salam; Dewi Novita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Reading skills were essential for students to understand various types of texts and master vocabulary. However, many students faced difficulties in comprehending English reading texts and showed low motivation for reading. To address this issue, this study aimed to test the effectiveness of the EWA (English with Apps) application as a digital learning medium for improving students' reading skills. The research employed a pre-experimental design with a one-group pretest-posttest model. The subjects of the study consisted of 35 students from class 10D at SMAN 1 Nanga Mahap. Data were collected through reading skills tests and analyzed using paired t-tests. The results showed that the average pre-test score of participants was 35.14, while the average post-test score increased to 44.86, with a difference of 9.71. Statistical analysis indicated that this difference was statistically significant with a p-value < 0.0001. These findings suggested that the use of the EWA application effectively improved participants' understanding, providing strong evidence of the positive impact of this intervention. The study concluded that a mobile-based EWA application is a promising approach to improving English reading skills in the context of secondary education. However, given the small pretest-posttest results, further research is needed in relation to this study